Bilobe parotid lipoma: a rare case report of parotid involving both the superficial and deep lobe with review of literature - Lamture, Y. R.; Tabrez, Md. Omar; Jaiswal, Shishir (International Surgery Journal, 2016)
Lipomas are common benign soft tissue tumours, they are found in every body part where the fat is normally present but they are rarely found in the head and neck region. There are few reports of parotid lipoma and till date only one case report of bilobe lipoma has been reported earlier. They compromise 0.6%-4.4% of all parotid tumour. A 60 year old male presented with a large swelling in left parotid region extending from left pre-auricular region to submandibular region from 6 years. Examination of the facial nerve was normal. Ultrasound of the region suggested of lipoma. Fine needle aspiration cytology was done which supported the ultrasounds diagnosis. Patient underwent tumour excision with facial nerve preservation. Lipoma of size 10 x 8 cm which is the largest reported bilobe parotid lipoma reported till date. Literature review has suggested lipomas of parotid region are rare hence should be kept in one of the differential diagnosis. Surgical intervention is challenging because of the probability of injuring the facial nerve, thus knowledge of the anatomy and meticulous surgical technique is essential.